The influence of competition time on soccer players' performance factors: a scoping review with evidence gap map - Milheiro, A.; Baptista, I.; Nakamura, F. Y.; Sarmento, H.; Clemente, F. M.; Silva, J. R.; Afonso, J. (Sports Medicine, 2026)
Background: Performance in team sports is influenced by physical, technical, tactical, and psychological factors. Understanding the disparities in playing time between starters and nonstarters is crucial for optimizing training strategies and performance management. Objectives: This systematic scoping review with an evidence gap map (EGM) aimed to (i) synthesize findings from studies comparing the performance factors of starters and nonstarters, (ii) identify compensatory strategies for players with reduced playing times and barriers to the implementation of these strategies, and (iii) provide an EGM to guide future research toward addressing the most relevant gaps in the literature. This review followed the PRISMA 2020 guidelines and the respective extension for scoping reviews (PRISMA-ScR). Electronic databases such as the Cochrane Library, PubMed, Scopus, SPORTDiscus, and Web of Science (Core Collection) were searched on 31/08/2023. The RoBANS tool was used to assess the risk of bias. Among 32,613 articles, 57 trials from 70 publications were included. Results: Female soccer players were represented in only 15.8% of the trials. The physical performance factor (k = 56, 98.2%) has been extensively studied in relation to the differences between starters and nonstarters. Few studies have analyzed technical and psychological performance factors, while tactical factors have not been addressed. Starters presented higher values of external absolute intensity (EAI, measured by the total distance and sprint distance), higher internal absolute intensity (IAI, assessed through heart rate-based measures as above 70% maximal heart rate), along with greater improvements in exercise performance measurements (countermovement jump and 20-m sprint), than nonstarters did. The most adopted categorization was based on match participation (k = 33, 57.9%), with starters defined as players who played for = 66.7% of a match time (14.0%). The day commonly used for compensatory training was 24 h after a match (k = 16; 37.5%). Several strategies attempting to reproduce competitive loads were used, such as small-sided games (k = 9; 56.3%), running-based drills (k = 8, 50.0%), small-positional games (k = 3, 18.8%), tactical-technical drills (k = 2, 12.5%), strength training (k = 2, 12.5%), and friendly matches (k = 1, 6.5%). Conclusion: This scoping review highlights the necessity of placing increased emphasis on technical, tactical, and psychological performance factors and compensatory training strategies (including the day and types of exercise). These measures aim to replicate the competitive match demands for nonstarters, maintaining or enhancing the physical adaptations, psychological factors, and tactical-technical skills required for performance improvement throughout the season. This review proposes three main future research areas for the topic: (i) investigating the effects of compensatory training on nonstarters` weekly loads when distributed across multiple days; (ii) investigating additional cutoffs or more refined time classifications for nonstarters; and (iii) directing more studies toward female soccer players.